Detection of Newcastle disease virus using a SYBR Green I real time polymerase chain reaction - Tan, Sheau Wei; Omar, Abdul Rahman; Ideris, Aini; Yusoff, Khatijah; Tan, Wen Siang (AEPress, 2004)
A two-step SYBR Green I real time polymerase chain reaction (PCR, real time PCR) for the detection of Newcastle disease virus (NDV) was developed. A melting curve analysis was performed to distinguish specific from non-specific products and primer dimmers. Regardless of different virus pathotypes the melting temperature (Tm) ranged from 86°C to 87°C. The sensitivity of the real time PCR was compared with the reverse transcription (RT) – nested PCR enzyme – linked immunosorbent assay (ELISA, RT-nested PCR ELISA). Whereas the detection limit of the real time PCR was 10 pg DNA, the RT-nested PCR ELISA and conventional PCR could only detect up to 1 ng and DNA, respectively. Thus the real time PCR offers a sensitive, rapid and convenient method for screening large number of NDV specimens.